Production of d-Lactate from Avocado Seed Hydrolysates by Metabolically Engineered Escherichia coli JU15 - Dulce María Palmerín-Carreño; Ana Lilia Hernández-Orihuela; Agustino Martínez-Antonio (Fermentation, 2019)
Agroindustry residues can be used to produce valuable chemicals such as lactic acid, which is a primary chemical platform with many industrial applications. Biotechnological processes are the main approach of lactic acid production; however, culture media has an important impact on their costs. As a result, researchers are exploring various methods of production that use residual or waste biomass as raw materials, most of which are rich in lignocellulose. Nevertheless, starch and micronutrients such as those contained in avocado seeds stand out as promising feedstock for the bioprocess as well. In this study, the lactogenic Escherichia coli strain JU15 was evaluated for producing d-lactate using an avocado seed hydrolysate medium in a controlled stirred-tank bioreactor. The highest lactic acid concentration achieved was 37.8 g L−1 using 120 g L−1 as the content of initial reducing sugars. The results showed that d-lactate can be produced from avocado seed, which hydrolysates to 0.52 g L−1 h−1 using the engineered E. coli JU15. This study may serve as a starting point to further develop bioprocesses for producing metabolites using avocado seed hydrolysates.